Literature Review: Pola Asuh Orang Tua terhadap Pertumbuhan Emosional Anak - Anisah Nur Asidah; Miftahul Janna; Rika Septiani; Teresia Suminta Rotua Situmoran (Lembaga Pengembangan Kinerja Dosen, 2025)
Children's emotional development during childhood is a very important basis in forming attitudes, values ​​and behavior in the future. Parenting styles play a very important role in the formation and emotional development of children. This research examines various types of parenting patterns applied by parents and their impact on children's psychological well-being. Based on literature analysis from ten journals, it was found that positive parenting styles, such as authoritative, can support the development of children's emotional regulation and self-confidence. On the other hand, authoritarian or permissive parenting can actually hinder a child's ability to express emotions in a healthy way. The results of this study show that early social experiences and a positive family environment greatly influence children's emotional development, which ultimately has an impact on their success in the future. This research highlights the importance of parental attention in implementing parenting patterns that support children's emotional